Modernitas Petani: Tingkat Modernitas Serta Hambatan Struktural Dan Budaya dalam Agribisnis Padi - A, Sasmita; S. Ali, Saleh; Amrullah, A. (Hasanuddin University, 2024)
This study aims to determine the level of modernity of rice farmers, identify agricultural modernization processes that encourage the modernity of rice farmers, and identify obstacles (structural and cultural) that hinder the modernity of rice farmers. This research was conducted in Timusu Village, Liliriaja District, Soppeng Regency, South Sulawesi. This research approach is a quantitative approach using survey methods through direct interviews with rice farmers and filling out questionnaires. The measurement of modernity uses the Likert scale and the data analysis used is descriptive statistical analysis. Based on the results of the Likert scale analysis on the level of modernity of rice farmers measured through fourteen indicators, an average total score of 147 and an average index of 69.95% were obtained, meaning that the level of modernity of rice farmers is in the high category. Agricultural modernization occurs when rice farming communities see farmers in other regions using modern agricultural technology. The presence of the use of modern agricultural technology can facilitate and speed up the completion of work. This encourages the modernity of rice farmers who are always interested in trying new things, as well as accepting change. The social relations and way of life of farmers began to change and adapt to today's connections and way of life. The barriers to modernity of rice farmers are divided into two parts: structural barriers and cultural barriers. Structural obstacles are caused by the narrow area of arable land and the institutional role of farmer groups is lacking in the management of alsintan use. Meanwhile, cultural barriers are caused by low farmer education and aging of farmers.